The hermeneutics of crisis : evangelicals, apocalypse and conflict in Northern Ireland Troubles - Searle, Joshua (Trinity College (Dublin, Ireland). School of English, 2012)
Apocalyptic eschatology sets us questions that lead us into the heart of the relationship between ideas and their expression in culture. The significance of apocalyptic eschatology becomes apparent upon a brief consideration of its immense existential scope. Human beings seem to possess an extraordinary capacity to rise above present adversity by looking forward to future possibilities out of which to create new horizons of hope.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.